Emission characteristics study of Gasoline-Diesel and Gasoline-Diesel/pentanol blend. Issue 1 (December 2020) - Mathavan, S; Mothilal, T; Dillibabu, V; Billy, D; Muthu, G
Abstract: Increase in vehicular emission affects the environment due to air pollution. Emission laws are formulated to control vehicular emission and all nations show their intensive interest in alternative fuel for pollution reduction and fuel economy. In the present work, experiment was carried out in a direct diesel inject 4-S engine; for diesel, Gasoline-Diesel and Gasoline-Diesel/pentanol blend (D70/P30). For dual fuel mode, Diesel is supplied from main injection and Gasoline was injected into the port at 5 bar. The result indicates high hydrocarbon emission at no load condition for both Gasoline-Diesel (1200 PPM) and Gasoline-Diesel/Pentanol blend (1170 PPM). Maximum NOx emission was observed for D70-P30 blend. Low CO emission (<2%), CO2 emission (<6%) and smoke emission (<70 PPM) was observed in blended fuel up to 60% load condition.